2019
DOI: 10.1029/2018ef001030
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Patterns of Crop Yield Change by Emitted Pollutant

Abstract: Field measurements and modeling have examined how temperature, precipitation, and exposure to carbon dioxide (CO 2 ) and ozone affect major staple crops around the world. Most prior studies, however, have incorporated only a subset of these influences. Here we examine how emissions of each individual pollutant driving changes in these four factors affect present‐day yields of wheat, maize (corn), and rice worldwide. Our statistical modeling indicates that for the global mean, climate and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…Impacts on labor are evaluated based on both exposure to air pollution and heat ( 15 , 34 , 36 ), the latter for specific professions where heat exposure is both difficult to avoid and impactful. Agricultural impacts include responses to temperature and precipitation and to changes in CO 2 and surface ozone ( 37 ). The analysis includes projected changes in population, baseline health, and gross domestic product but does not include changes in the workforce or cultivated areas ( SI Appendix ).…”
Section: Methodsmentioning
confidence: 99%
“…Impacts on labor are evaluated based on both exposure to air pollution and heat ( 15 , 34 , 36 ), the latter for specific professions where heat exposure is both difficult to avoid and impactful. Agricultural impacts include responses to temperature and precipitation and to changes in CO 2 and surface ozone ( 37 ). The analysis includes projected changes in population, baseline health, and gross domestic product but does not include changes in the workforce or cultivated areas ( SI Appendix ).…”
Section: Methodsmentioning
confidence: 99%
“…For example, two CTM-based studies estimated 2005 respiratory-related premature mortalities in the USA using the same relative risk function (Jerrett et al, 2009), yet yielded results that differed by ∼ 3× (i.e., 13 000 vs. 38 000; Zhang et al, 2018;Lelieveld et al, 2013). While CTMs accurately reproduce many features of atmospheric chemistry (Shindell et al, 2013;Hu et al, 2018), one important issue associated with CTM-based impact assessments is that CTMs are consistently biased high when predicting O 3 concentrations (e.g., Schnell et al, 2015;Travis et al, 2016;Yan et al, 2016;Seltzer et al, 2017, Porter et al, 2017Guo et al, 2018). Such biases can influence estimates of impacts and are often amplified by nonlinear concentrationresponse functions .…”
Section: Introductionmentioning
confidence: 99%
“…Future warming would also go along with rising atmospheric CO2CO2 fertilization may partially offset the warming damages. A recent study indicated that in temperate regions, CO2 emissions would cause a substantial short‐term increase in agricultural production due to the instantaneous response of atmospheric CO2 concentrations to emissions, but the net effect attenuates within a decade or so to near‐zero as the CO2 fertilization is canceled by the impacts of CO2‐induced climate change (Shindell et al., 2019). Greater atmospheric CO2 concentration induced by future fossil fuel combustion brings an offset of global warming on crop yields, and should be integrated into future analysis.…”
Section: Resultsmentioning
confidence: 99%